Perbandingan Pemanfaatan Teknologi Informasi dan Komunikasi dalam Pendidikan Dasar di Indonesia dan Malaysia: (Studi Literatur Sistematis Tahun 2021–2025) - Mukhoddasyah, Radina; Hendrayadi, Eka; Abdalina; Wahyuni, Eka; Lubis, Hasrita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze and compare the utilization of Information and Communication Technology (ICT) in primary education between Indonesia and Malaysia through a systematic literature review. The research explores trends, strategies, and challenges faced by both countries in integrating ICT to improve learning quality and student engagement. Ten scientific articles published between 2021 and 2025 were analyzed, consisting of five from SINTA-indexed national journals and five from Scopus-indexed international journals. The results reveal that both Indonesia and Malaysia have made significant progress in ICT integration, but with different approaches. Indonesia emphasizes classroom-based and teacher-initiated innovation, while Malaysia applies top-down national policies that strengthen digital infrastructure and teacher competency frameworks. Key challenges include digital divides, limited teacher skills, and insufficient infrastructure. The findings suggest the importance of continuous teacher professional development, equitable access to ICT facilities, and cross-country collaboration to enhance ICT-based primary education in Southeast Asia.